Pendidikan dan Pelatihan Memoderasi Pengaruh Teknologi Informasi dan Kemampuan Pemakai Pada Kinerja Sistem Informasi Akuntansi - Widiantari, Ni Made Sulastri; Mertha, Made (E-Jurnal Akuntansi; Vol 22 No 1 (2018), 2018)
Information systems have an important role in an organization or company because the information becomes a tool in determining decisions. Information obtained is expected to be accurate information, has the right value and relevant, and available on time, whenever necessary. Such information can be generated by computer-based information systems. Information is useful data that is processed in order to become a guide for making the right decisions. One of the tools of information presentation is accounting. Accounting information system is very useful to achieve efficiency and effectiveness in determining decisions The use of computer-based accounting information system is very important applied in the BPR to produce information in the form of relevant financial statements, accurate and timely. This study aims to prove empirically that education and training to moderate the influence of information technology and the ability of users on the performance of accounting information systems. The number of samples taken as many as 48 respondents who are employees who work using computerized SIA based on the technique of non-probability sampling, namely by saturated sampling method. Data analysis technique used is multiple linear regression test and interaction test of Moderated Regression Analysis (MRA). Based on the analysis result, information technology and user ability have positive and significant influence on SIA performance, education and training can moderate the influence of information technology on SIA performance, but education and training are not able to moderate the influence of user ability on SIA performance in BPR Klungkung District  Keywords: Information technology, user capability, education and training, SIA performance